Resource-based view of barriers and drivers to the survival of Small and Medium-sized Enterprises (SMEs) in rural areas of Centane in the Eastern Cape, South Africa - Fadana-Dumani, Akhona Pumza (Rhodes University, Faculty of Commerce, Rhodes Business School)
This research study set out to analyse the barriers and drivers of small business survival in rural areas of Centane. Small and Medium sized Enterprises (SME's) are considered a crucial element in achieving economic growth as well as job creation. These businesses play a pivotal role in the improvement of rural economy and livelihood and their existence is intricately linked to the survival of the local communities. Hence, the study seeks to analyse the barriers experienced by rural SME's, resources and interventions required to be successful, was conducted in Centane, a rural town situated in Mnquma Local Municipality, Amathole District Municipality, Eastern Cape Province, The Resource based theory framework was employed to better understand the selected case study. A semi-structured questionnaire was developed in English then translated into isiXhosa the local vernacular to easy the information flow and ensures the respondent confidence during the face-to-face interview. The interviews were randomly conducted to fourteen (14) key informants (SME's). The data was analysed using thematic analysis. Results indicated that the inadequate infrastructure, lack of skills and training as well as funding and support from the government are the key barriers experienced by the SME's. Furthermore, results showed that critical skills such as business, records, financial management as well as marketing are required to ensure the sustainability of the SME's in this area. Through the integration of Resource-Based-Framework, the study revealed the significance, and the availability of both the tangible and intangible resources in shaping the competitive-edge, survival and the sustainability of SME's in Centane. The involvement of local government and other related development agencies is recommended to actively participate and play a more active role in ensuring the development, survival, sustainability and success of the SME's in this area. Their intervention should be through facilitation of trainings and skills development initiatives with special focus on financial, marketing and business-related skills.
Keywords: Small and medium enterprises; Small business -- South Africa -- Eastern Cape; Intangible property; Barriers to entry (Industrial organization); Driver